Nonstandard peptide binding revealed by crystal structures of HLA-B*5101 complexed with HIV immunodominant epitopes. - Maenaka, K; Maenaka, T; Tomiyama, H; Takiguchi, M; Stuart, D; Jones, E (2000)
The crystal structures of the human MHC class I allele HLA-B*5101 in complex with 8-mer, TAFTIPSI, and 9-mer, LPPVVAKEI, immunodominant peptide epitopes from HIV-1 have been determined by x-ray crystallography. In both complexes, the hydrogen-bonding network in the N-terminal anchor (P1) pocket is rearranged as a result of the replacement of the standard tyrosine with histidine at position 171. This results in a nonstandard positioning of the peptide N terminus, which is recognized by B*5101-restricted T cell clones. Unexpectedly, the P5 peptide residues appear to act as anchors, drawing the peptides unusually deeply into the peptide-binding groove of B51. The unique characteristics of P1 and P5 are likely to be responsible for the zig-zag conformation of the 9-mer peptide and the slow assembly of B*5101. A comparison of the surface characteristics in the alpha1-helix C-terminal region for B51 and other MHC class I alleles highlights mainly electrostatic differences that may be important in determining the specificity of human killer cell Ig-like receptor binding.